2015
DOI: 10.1007/s10802-015-9976-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Load Differentially Impacts Response Control in Girls and Boys with ADHD

Abstract: Children with attention-deficit hyperactivity disorder (ADHD) consistently show impaired response control, including deficits in response inhibition and increased intrasubject variability (ISV) compared to typically-developing (TD) children. However, significantly less research has examined factors that may influence response control in individuals with ADHD, such as task or participant characteristics. The current study extends the literature by examining the impact of increasing cognitive demands on response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 82 publications
(151 reference statements)
5
57
0
Order By: Relevance
“…For example, prior studies have shown that motor control deficits are more prominent in boys than in girls with ADHD (Cole, Mostofsky, Larson, Denckla, & Mahone, 2008), whereas impairments in working memory and related EFs are present in both boys and girls with the disorder (Rucklidge, 2010). Consistent with these earlier studies, recently published findings in a large sample of girls and boys with ADHD compared to typically developing (TD) children found evidence of impaired response control in boys with ADHD across tasks with varied cognitive demand, whereas girls with ADHD only performed more poorly when working memory was necessary to guide response selection (Seymour, Mostofsky, & Rosch, 2015). In addition, a recent structural neuroimaging study found evidence of reduced cortical surface area in premotor regions in boys, but not girls, with ADHD, and more widespread surface area reductions in prefrontal regions in girls compared to boys with ADHD (Dirlikov et al, 2015).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…For example, prior studies have shown that motor control deficits are more prominent in boys than in girls with ADHD (Cole, Mostofsky, Larson, Denckla, & Mahone, 2008), whereas impairments in working memory and related EFs are present in both boys and girls with the disorder (Rucklidge, 2010). Consistent with these earlier studies, recently published findings in a large sample of girls and boys with ADHD compared to typically developing (TD) children found evidence of impaired response control in boys with ADHD across tasks with varied cognitive demand, whereas girls with ADHD only performed more poorly when working memory was necessary to guide response selection (Seymour, Mostofsky, & Rosch, 2015). In addition, a recent structural neuroimaging study found evidence of reduced cortical surface area in premotor regions in boys, but not girls, with ADHD, and more widespread surface area reductions in prefrontal regions in girls compared to boys with ADHD (Dirlikov et al, 2015).…”
Section: Introductionsupporting
confidence: 63%
“…However, motivational contingencies improved ISV among TD children despite strong baseline performance. Findings from a recent study (Seymour et al, 2015) suggest that impaired response control among girls with ADHD is only present during a task with greater executive function demands, during which working memory was necessary to guide response control, but not during a response control task with minimal cognitive demands. In contrast, boys with ADHD demonstrated elevated ISV during tasks with minimal and greater cognitive demands, as shown in a previous study (Seymour et al, 2015) and on both the standard and motivational GNG compared to TD boys in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also reported sex differences in neuropsychological functioning in children with ADHD (Hasson & Fine, 2012; O’Brien, Dowell, Mostofsky, Denckla, & Mahone, 2010; Seymour, Mostofsky, & Rosch, 2015; Wodka et al, 2008), with girls generally showing more deficits in planning and strategy mediated by prefrontal circuits, and boys showing greater impairments in more basic aspects of response control mediated by motor/ premotor circuits. Two recent studies revealed a sexually dimorphic effect of working memory demands (Seymour et al, 2015) and reinforcement (Rosch, Dirlikov, & Mostofsky, 2015) on response control. Specifically, girls with ADHD only displayed impaired response control under conditions of greater working memory demands, whereas response control was impaired among boys with ADHD regardless of working memory demands (Seymour et al, 2015).…”
Section: Introductionmentioning
confidence: 99%